MODERNIZATION OF THE HIGHER TECHNICAL SCHOOL: HISTORICAL EXPERIENCE AND PROSPECTS - E. V. Bodrova; N. B. Golovanova (Российский технологический журнал)
In article on the basis of published and previously unpublished documents and materials explores the basic conceptual approaches, stages and results of the reform of the higher technical school of Russia in the context of modernization processes. We conclude unresolved significant part of the planned tasks in the first stages of reforms in this area because of a miscalculation of the authors in developing the concept of reforms and inaccurate their chosen strategy of socio-economic development of the country. In the 1990s high school functioned in survival mode while trying to adapt to market conditions. At the beginning of the XX1 century, despite the increased funding and the introduction of new programmes and forms of training, to achieve a significant increase in the quality of engineering education has failed. Sharp enough remained the problem of employment of graduates. Milestone was 2015, when the role of quality training of engineers was designated as the basic conditions of economic development of the country. The article stated some achievements in the implementation of major projects of the Ministry of science and education in recent years. The author argues the need for: involving the development of conceptual frameworks of modernization of the higher technical school University community; the accumulation of all of the positive foreign and domestic experience in conducting such reforms.